2021
DOI: 10.3390/foods10122905
|View full text |Cite
|
Sign up to set email alerts
|

Glycidol Fatty Acid Ester and 3-Monochloropropane-1,2-Diol Fatty Acid Ester in Commercially Prepared Foods

Abstract: Glycidyl fatty acid esters (GEs), which are the main pollutant in processed oils, are potential mutagens or carcinogens. 3-Monochloropropane-1,2-diol fatty acid esters (3-MCPDEs) are also well-known food processing contaminants. 3-MCPDEs are believed to be a precursor to GEs in foodstuffs. In vivo, lipase breaks down the phosphate ester of GEs and 3-MCPDEs to produce glycidol and 3-MCPD, respectively, which are genotoxic carcinogens. Thus, it is important to determine human exposure to GEs and 3-MCPDEs through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…The levels of 2-MCPDEs in lipids of fried rice were 0.38 and 0.39 mg/kg before and after cooking, while those of their GEs were 1.44 and 1.42 mg/kg, respectively. Shimamura et al 30) reported the levels of 3-MCPDEs in commercial fried rice was 0.048 mg/kg. Our result was higher than their data.…”
Section: Fried Ricementioning
confidence: 99%
“…The levels of 2-MCPDEs in lipids of fried rice were 0.38 and 0.39 mg/kg before and after cooking, while those of their GEs were 1.44 and 1.42 mg/kg, respectively. Shimamura et al 30) reported the levels of 3-MCPDEs in commercial fried rice was 0.048 mg/kg. Our result was higher than their data.…”
Section: Fried Ricementioning
confidence: 99%
“…The presence of both 3-MCPD and 3-MCPDE in food was first suggested in 2004 . Later, 3-MCPDE was widely found in foods such as refined cooking oils, infant formula, fried potato chips, fried bread, salted biscuits, roasted coffee, and so on, and the level of 3-MCPDE was higher than the corresponding 3-MCPD . Studies have shown that 3-MCPDE in processed foods, such as coffee creamers, is mainly derived from the oil in the formulation .…”
Section: Hot Research Topics On 3-mcpdementioning
confidence: 99%
“…This finding indicates that humans are exposed to GEs from sources other than DAG oil. Besides being food contaminants found at highest levels in refined vegetable oils and fats, GEs are found in cooked meat and fish [ 17 ], as well as prepared foods such as instant noodles, fried chicken, and fried confectionery as new sources [ 18 ]. In particular, high concentrations of GEs were detected in meat cooked on charcoal that can be heat treated at high temperatures.…”
Section: Introductionmentioning
confidence: 99%